2022
DOI: 10.7554/elife.66169
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of threat learning reveals links with anxiety and neuroanatomy in humans

Abstract: Influential theories implicate variations in the mechanisms supporting threat learning in the severity of anxiety symptoms. We use computational models of associative learning in conjunction with structural imaging to explicate links among the mechanisms underlying threat learning, their neuroanatomical substrates, and anxiety severity in humans. We recorded skin-conductance data during a threat-learning task from individuals with and without anxiety disorders (N=251; 8-50 years; 116 females). Reinforcement-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…One explanation may be that fear-related symptoms and disorders are more related to these learning differences than distress-related disorders (Clark & Watson, 1991;McTeague & Lang, 2012b). Other learning differences in the studies reviewed in Table 2 indicate differences in learning from good versus bad outcomes, but this learning impairment also appears in studies of depression (Abend et al, 2022;Brown et al, 2021;Gagne et al, 2020;Lamba et al, 2020;Wise & Dolan, 2020). The direction of results in individual studies varies; a recent computational meta-analysis suggested that anxiety and depression show greater punishment learning rates (Pike & Robinson, 2022).…”
Section: D Reinforcement Learning Studies Of Anxietymentioning
confidence: 99%
“…One explanation may be that fear-related symptoms and disorders are more related to these learning differences than distress-related disorders (Clark & Watson, 1991;McTeague & Lang, 2012b). Other learning differences in the studies reviewed in Table 2 indicate differences in learning from good versus bad outcomes, but this learning impairment also appears in studies of depression (Abend et al, 2022;Brown et al, 2021;Gagne et al, 2020;Lamba et al, 2020;Wise & Dolan, 2020). The direction of results in individual studies varies; a recent computational meta-analysis suggested that anxiety and depression show greater punishment learning rates (Pike & Robinson, 2022).…”
Section: D Reinforcement Learning Studies Of Anxietymentioning
confidence: 99%
“…However, learning to accurately respond to a threat requires multiple learning episodes to appropriately understand threat contingencies. Deficits in appropriate threat identification or threat response can lead to behavioral outcomes resembling an anxiety disorder (Abend et al, 2022;Britton et al, 2011;Robinson et al, 2013). Consequently, fearand anxiety-related disorders are often thought to be characterized by aberrations in threat processing and conditioning (Craske et al, 2017;Fenster et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently 1 , the understanding of cognitive and neural mechanisms related to fear and anxiety has depended on experimental paradigms in which the impact of fear-inducing stimuli on behavior and neural activity can be investigated in the laboratory. Despite their elegance and continuing and critical importance 2 , such paradigms do not capture an important feature of fear-related behavior in the everyday lives of humans and other animals: the balancing of attention between threat and reward. In everyday life people must attend vigilantly to stimuli that presage adverse events but also to the stimuli predictive of positive events.…”
Section: Introductionmentioning
confidence: 99%